STUDY OF VARIOUS TYPES OF AESTHETIC ELEMENTS ON ARCHITECTURAL STYLES FACADE OF CHURCH ST. YUSUF CIREBON - Theresia Pynkyawati; Chandra Yuli K. (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
St. Yusuf 's Church located in Cirebon City is included in one of the oldest catholic church colonial buildings in West Java with a function as a gathering place and a place of worship for Christians. The church has an interesting facade in every part, starting from the roof, walls, columns and not too much use of such complicated ornaments. The facade of St. Yusuf 's Church certainly has a variety of types that affect the appearance of the facade in terms of aesthetic elements used as supporting elements and characteristics of a facade which is usually found in all colonial buildings in Indonesia. The various types of aesthetic elements on the facade of St. Yusuf 's Church are categorized into three parts, namely the head, body, and legs which are then influenced by architectural styles. This research was conducted using a qualitative descriptive analysis method by tracing the aesthetic elements on the facade of the building against the theory of architectural style. The results of the study showed that several types of aesthetic elements on the facades of Church buildings were included in colonial styles, indische empires, Romanesque with gothic and art deco touches.